The gardener and the carpenter : what the new science of child development tells us about the relationship between parents and children - Gopnik, Alison (Farrar, Straus and Giroux, 2016)
"Caring deeply about our children is part of what makes us human. Yet the thing we call 'parenting' is a surprisingly new invention. In the past thirty years, the concept of parenting and the multibillion dollar industry surrounding it have transformed child care into obsessive, controlling, and goal-oriented labor intended to create a particular kind of child and thereby a particular kind of adult. In The Gardener and the Carpenter, the pioneering developmental psychologist and philosopher Alison Gopnik argues that the familiar twenty-first-century picture of parents and children is profoundly wrong--it's not just based on bad science, it's bad for kids and parents, too. Drawing on the study of human evolution and her own cutting-edge scientific research into how children learn, Gopnik shows that although caring for children is immensely important, the goal should not be to shape them so they turn out a particular way. Children are designed to be messy and unpredictable, playful and imaginative, and to be very different both from their parents and from one another. The variability and flexibility of childhood allow them to innovate, create, and survive in an unpredictable world. “Parenting" won't make children learn--rather, caring parents let children learn by creating a secure, loving environment."--Dust jacket.